IMPLEMENTASI NILAI-NILAI PANCASILA PADA PENDIDIKAN KARAKTER GOTONG ROYONG DI SMA PUSPITA KABUPATEN BANYUASIN - Sunaryo Sunaryo; Isnaini Muslimah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The moral development and character of the nation is closely related to the improvement of the quality of education development and the improvement of people's welfare. In connection with the implementation of education, the government has determined to make education as the main foundation in fostering and nurturing the positive character of the nation. This study used qualitative descriptive. This research helps to find the character gotong royong (Work Hard) on student self done in SMA Puspita Kecamatan Air Kumbang Banyuasin Regency. Data obtained through documentation, observation, and interviews with Principal SMA Puspita. The results of this study explained that in SMA Puspita Kecamatan Air Kumbang Banyuasin district students have a character of hard work through mutual assistance activities. Based on the character obtained from Pancasila which is interpreted from the third principle of the unity of Indonesia which is a form of mutual cooperation.